Pemanfaatan Limbah Kelapa Sawit Melalui Pengolahan Biologis dalam Rangka Integrasi Industri Kelapa Sawit dan Ternak Ruminansia - Liman, Liman; A., Kusuma; Widodo, Yusuf (Jurnal Penelitian Pertanian Terapan, 2010)
The aims of the research was to identified effect of biological processing of the palm oil by product on nutrient parameters on ruminant. Fungi was used in this research was Sacharomyces cerevicae . After the processing, palm oil by product was added into basal rations. Latin square design was used . The research used four cattle as matterial trial . The treatments was arranged R0= basal rations (70 % consentrate+30% forage), Rz=85% basal rations+15% combinations of palm press fiber and palm oil sludge, R2= 70% basal rations+30% combinations of palm press fiber and palm oil sludge, R3=55 % basal rations+ 45% combinations of palm press fiber and palm oil sludge. The result showed that the treatments had no significant effect on rumen parameters and dry matters consumptions (P<0.05). Digestibility parameters had significant effect (P>0,05). Based on least significant different test, substitution palm oil by product on 30 to 45% could decreasing nutrient digestibility both dry matter, organic matter, protein, and crude fiber. Based on nutrient digestibility parameters, palm oil by product can be used up to 15%. Keywords : Palm oil by product, digestibility